A flipped classroom in communication systems: Student perception and performance assessments. Issue 3 (July 2019) - Öncel, Aksay Fatih; Kara, Ali
Flipped classroom is an emerging course delivery method, where the traditional in-class and out-of-class activities flip places. The lectures are given out-of-class with electronic resources and in-class time is reserved for group activities and discussion with the instructor. In this study, we present our implementation of a flipped classroom in a senior level undergraduate engineering course. An extensive perception analysis was carried out with anonymous surveys and face-to-face interviews with students. Performance analysis of the flipped class was carried out by comparing the achievement level in the course learning outcomes of previous years' traditional classes and recent year's flipped class. The out-of-class lectures were implemented as machine-voice-narrated presentations. The effect of machine voice on the flipped classroom is also examined. Students' perception and reaction to various aspects of the flipped class are documented. Performance analysis showed a significant improvement in one category of course learning outcomes. Student perception was positive overall.